Correlation of Brain-Derived Neurotrophin Factor Levels in Epilepsy Patients Treated with Valproic Acid and Phenytoin with Cognitive Function - Madi, Kharis; Bintoro, Aris Catur; Samekto, M. I. Widiastuti; Kustiowati, Endang; Muhartomo, Hexanto; Diah, Elta (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Epilepsy cases requiring OAE multitherapy are found in 40% of total epilepsy cases. Many epilepsy patients are referred to Dr. Kariadi Hospital Semarang because of the occurrence of intractable epilepsy. Valproic acid is one of the OAEs that are widely used in the BPJS era in Indonesia as a combination of phenytoin. Seizures increase the expression of BDNF mRNA and protein. METHODS: This study is a cross-sectional study that took place from January to May 2022. The subjects of this study were epilepsy patients who used a combination of phenytoin-valproic acid who met the inclusion criteria. Patient data were obtained from medical records and filling out questionnaires. Patients were asked to fast for ± 8−10 h. Furthermore, blood sampling (±5 ml) of BDNF was carried out at 08.00−10.00 WIB. Cognitive function assessments were performed using MoCA-Ina and the Hamilton depression rating scale at the same time. Data were analyzed by Spearman correlation test and partial correlation test. The results are said to be meaningful if p < 0.05. RESULTS: Thirty-two study subjects used a combination of phenytoin-valproic acid. The Spearman correlation test between the relationship between BDNF levels and cognitive function in epilepsy patients treated with valproic acid and phenytoin showed a significant relationship with the direction and strength of which was strongly positive (r = 0.676 and p ≤ 0.001). The partial correlation test between the relationship between BDNF levels and cognitive function after controlling for age (r = 0.692), seizure frequency (r = 0.641), duration of combination therapy (r = 0.700), and age of seizure onset (r = 0.693) remained the same, while after controlling for the level of education (r = 0.812) and the type of seizure (r = 0.747) increased. CONCLUSION: There is a strong correlation between BDNF levels and cognitive function in epilepsy patients treated with valproic acid and phenytoin. The relationship between BDNF levels and cognitive function remained the same after controlling for age, frequency of seizures, duration of combination therapy, and age of onset of epilepsy.